KOLABORASI STAKEHOLDER DALAM PENGEMBANGAN EKOWISATA MANGROVE PANTAI KERTOMULYO KECAMATAN TRANGKIL KABUPATEN PATI - Khusnul Khuluqi, Muhammad; Suwitri, Sri; Afrizal, Teuku (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Kertomulyo Beach Ecotourism has a long history and eventually gained advantages over other beaches in Pati Regency. The progress of Kertomulyo Beach Ecotourism has been achieved through collaboration between the government, private sector, and the community, as stated in Regional Regulation No. 2 of 2018 concerning the Pati Regency Tourism Development Plan 2018-2025. The purpose of this study is to identify the stakeholders involved and the collaboration processes occurring at Kertomulyo Beach. The method used is descriptive qualitative. Some of the theories applied include stakeholder mapping matrix vs. interest theory and stakeholder collaboration processes. The subjects of the study were determined using purposive sampling techniques. The research results focus on the study's objectives, yielding two main conclusions.The first conclusion shows that the stakeholders involved are categorized into four groups based on their level of importance and power: crowd, contest setter, subject, and player. No stakeholders were identified in the crowd category. The contest setter stakeholder is the Pati Regency Tourism, Youth, and Sports Agency (DINPORAPAR). The subject category includes traders, the community, village administration, and mass media. Finally, the player category includes PPUP, Tresno Segoro, and Misaja.The second conclusion indicates that overall, the collaboration process at Kertomulyo Beach can be considered good in terms of the transformation of the beach from barren to green, and its official designation as a tourist spot in 2017. However, in terms of tourism, the results are not significant, as evidenced by a decline in visitor numbers and issues in the collaboration process. Recommendations include enhancing collaboration in tourism at Kertomulyo Beach. Other issues, such as synergy between managers and village administration, must be addressed promptly to support sustainable ecotourism.Keywords: Collaboration, Stakeholder, Ecotourism.